PENILAIAN KINERJA PEGAWAI HONOR MENGGUNAKAN METODE BEHAVIORALLY ANCHOR RATING SCALE (BARS) DI PUSKESMAS HULONTHALANGI KOTA GORONTALO - Tarigan, Sylva Flora NInta; Simatupang, Rudolf (Fakultas Ilmu Kesehatan Universitas Siliwangi, 2024)
A good performance appraisal system can help identify employee strengths and weaknesses, provide constructive feedback, and encourage increased skills and motivation. Appraising the performance of honorary employees using the Behaviorally Anchored Rating Scale (BARS) method provides clarity and objectivity in assessing various aspects of employee behavior and skills. The aim of the research is to determine the performance assessment of honorary employees using the Behaviorally Anchor Rating Scale (Bars) method at the Hulonthalangi Community Health Center, Gorontalo City. The research method used a descriptive design, the population in the study were all honorary employees at the Hulonthalangi Community Health Center and the total sample was 17 people. This research uses a descriptive design. The sample in this research was 17 honorary employees. The independent variables in this research are discipline, responsibility, team work, problem solving and decision-making skills, obedience, honesty, self-motivation which are assessed using the Behaviorally Anchored Rating Scale (BARS) method, while the dependent variable is employee performance, which is measured using the Behaviorally Anchored Rating Scale (BARS) method. questionnaire. The results of this research found that the Behaviorally Anchor Rating Scale (BARS) performance assessment included 3 factors, including factor 1 discipline with a weight of 1,851, factor 2 Responsibility with a weight of 1,377, factor 3 Team Work with a weight of 1,067. It is recommended to conduct research related to employee performance to add other research variables.